Protective Effect of Galectin-1 during Histoplasma capsulatum Infection Is Associated with Prostaglandin E2 and Nitric Oxide Modulation - Rodrigues, Lï¿½lian Cataldi; Secatto, Adriana; Sorgi, Carlos A.; Dejani, Naiara N. [UNESP]; Medeiros, Alexandra I. [UNESP]; Prado, Morgana Kelly Borges; Ramos, Simone Gusmï¿½o; Cummings, Richard D.; Stowell, Sean R.; Faccioli, Lï¿½cia Helena; Dias-Baruffi, Marcelo (Hindawi, 2016)
Histoplasma capsulatum is a dimorphic fungus that develops a yeast-like morphology in host's tissue, responsible for the pulmonary disease histoplasmosis. The recent increase in the incidence of histoplasmosis in immunocompromised patients highlights the need of understanding immunological controls of fungal infections. Here, we describe our discovery of the role of endogenous galectin-1 (Gal-1) in the immune pathophysiology of experimental histoplasmosis. All infected wild-type (WT) mice survived while only 1/3 of Lgals1-/- mice genetically deficient in Gal-1 survived 30 days after infection. Although infected Lgals1-/- mice had increased proinflammatory cytokines, nitric oxide (NO), and elevations in neutrophil pulmonary infiltration, they presented higher fungal load in lungs and spleen. Infected lung and infected macrophages from Lgals1-/- mice exhibited elevated levels of prostaglandin E2 (PGE2, a prostanoid regulator of macrophage activation) and prostaglandin E synthase 2 (Ptgs2) mRNA. Gal-1 did not bind to cell surface of yeast phase of H. capsulatum, in vitro, suggesting that Gal-1 contributed to phagocytes response to infection rather than directly killing the yeast. The data provides the first demonstration of endogenous Gal-1 in the protective immune response against H. capsulatum associated with NO and PGE2 as an important lipid mediator in the pathogenesis of histoplasmosis.